Eco-friendly synthesis of Solanum trilobatum extract-capped silver nanoparticles is compatible with good antimicrobial activities - Ramanathan, S. (Elsevier B.V., 2018)
This study focused on the evaluation of antimicrobial activity of silver nanoparticles (AgNPs) after their green synthesis by means of a Solanum trilobatum bark extract. The obtained product with an intense surface plasmon resonance band at â¼442 nm with UVâvisible spectroscopic analysis indicated the formation of AgNPs. The morphology of AgNPs was observed under transmission electron microscopy and field emission scanning electron microscopy, displayed that the eco-friendly synthesized AgNPs have a spherical shape with an average size of â¼25 nm in diameter. X-ray powder diffraction and selected area electron diffraction analyses confirmed that the AgNPs are crystalline in nature. Fourier transform infrared spectroscopy indicated that the AgNPs capped with active ingredients of the bark extract. X-ray photoelectron spectroscopy revealed elemental composition of the AgNPs. The performance of S. trilobatum bark extract-capped AgNPs in terms of inhibition of microbial growth was studied by disc diffusion and well diffusion assays. Eco-friendly synthesized S. trilobatum extract-capped AgNPs were found to possess enhanced antimicrobial properties: growth inhibition of gram-negative and gram-positive bacteria and of fungal species. These results demonstrated the potential applications of the indigenous medicinal plants to the field of nanotechnology. Â© 2018 Elsevier B.V.